Investigation of Cutting Rock by TBM Hob using a SPG Method - Zhang, Xuhui; Tan, Tao; Hu, Dingbang; Li, Mi; Lin, Laikuang; Lin, Shun (Periodica Polytechnica Civil Engineering, 2022)
TBM (tunnel boring machine) hob is the core component of the TBM for rock cutting, whose cutting performance can directly determine the overall tunneling efficiency of the TBM. The understanding of cutting rock caused by TBM hobs is still not enough due to the complex contact features between the TBM hob and rock. To study the dynamic cutting process of the TBM hobs deeply, the rock cutting numerical model of the TBM hob is built based on the SPG (smooth particle Galerkin) method, the influence of hob penetration and hob spacing on rock breaking dynamic process, rock cutting forces and specific energy consumption are investigated. The results indicate that the dynamic process of sequential cutting of TBM hobs can be simulated well, and the rock breaking patterns caused by TBM hobs can be reflected with the SPG method. It also shows that the cutting forces of the hob are positively correlated with the hob penetration and hob spacing. For a given hob penetration, there exists an optimum hob spacing to acquire the highest rock cutting efficiency. The hob penetrations of 5, 7, 9, and 11 mm correspond to the optimum hob spacing of 60, 80, 90, and 100 mm respectively. Finally, the simulated results based on the SPG method are verified by comparing the experimental results and the CSM model. This study can provide a new method for simulating the rock cutting dynamic process of the TBM hobs.